GALERI TANAMAN HIAS DI MAKASSAR PENDEKATAN ARSITEKTUR MODERN - Ulandari, Surya; Arfan, Taufik (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Makassar city requires a place of gallery to preserve various types of ornamental plants and also provided various supporting facilities for lovers of ornamental plants, especially urban communities Makassar. Other factor that influence the appearance of the idea to plan the gallery of ornamental plants and also increase public interest toward the manufacture of garden plants that need supported by the container provision of adequate shopping ornamental plants, and become a need of life besides the primary requirement has been fulfilled also need to preserve and cultivate various types of ornamental plants in order to avoid extinction. It needs to be made